Chemisorbed Thiols on Silica Particles: Characterization of Reactive Sulfur Species - Caregnato, Paula (2010)
Silica particles with surface thiol groups (Sil-SH) were prepared by silylation of silanol groups using 3-mercaptopropyltrimethoxysilane. The particles were characterized by FTIR, Raman, and XPS spectroscopies; thermogravimetry; and solid state 13C and 29Si NMR spectroscopy. Laser flash excitation at 266 nm of Sil-SH water suspensions in the presence of sodium peroxodisulfate generated sulfur-centered radicals that were attached to the silica surface. These radicals were detected at their absorption maxima (330 nm) by transient optical techniques. Absorbance decay signals were fit to first- and second-order decay kinetics and were assigned to thiyl radicals. Formation of disulfide radicals, a major decay channel for free thiyl radicals in solution, was not observed for surface-grafted thiyl radicals.